1999
DOI: 10.1002/(sici)1521-3803(19990601)43:3<175::aid-food175>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive antinutritional peptides derived from cereal prolamins: A Review

Abstract: Alcohol-soluble endosperm proteins (prolamins) from some cereals (e.g. wheat, barley, and rye) give origin upon proteolytic digestion to biologically-active antinutritional peptides able to adversely affect in vivo the intestinal mucosa of coeliac patients, whereas prolamins from other cereals (e.g. maize and rice) do not. These antinutritional peptides are also able to: (a) prevent in vitro recovery of atrophic coeliac mucosa; (b) to inhibit differentiation of isolated rat fetal and chick fetal intestines; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…While cell proliferation is promoted by peptides from fish (Ravallec Ple et al 2001;Ravallec Ple et al 2000), soybean (Franek et al 2000), wheat (Franek et al 2000), and milk (Kayser and Meisel 1996), cell growth inhibition by peptides derived from soybean (Kops et al 1997) and milk (Ganjam et al 1997) has been described. Peptides derived from wheat have been found to inhibit (Giovannini et al 2000;Silano and De Vincenzi 1999) and promote (Rivabene et al 1999;Rocca et al 1983) cell death. Short-chain peptides with diverse biological properties, including cell growth regulation, can be released from food proteins during digestion and in vitro hydrolysis (Meisel and Bockelmann 1999;Vioque et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While cell proliferation is promoted by peptides from fish (Ravallec Ple et al 2001;Ravallec Ple et al 2000), soybean (Franek et al 2000), wheat (Franek et al 2000), and milk (Kayser and Meisel 1996), cell growth inhibition by peptides derived from soybean (Kops et al 1997) and milk (Ganjam et al 1997) has been described. Peptides derived from wheat have been found to inhibit (Giovannini et al 2000;Silano and De Vincenzi 1999) and promote (Rivabene et al 1999;Rocca et al 1983) cell death. Short-chain peptides with diverse biological properties, including cell growth regulation, can be released from food proteins during digestion and in vitro hydrolysis (Meisel and Bockelmann 1999;Vioque et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] This does not seem to be true for the remaining HLA-DQ8 determinant which belongs to a glutenin molecule. 17 We aimed to transfer these observations to a more complex system represented by the in vitro organ culture of coeliac biopsies, a model already used in the past to test the biological properties of gliadin peptides 14 and, more recently, their immunogenicity. 10 13 Our data showed that the DQ8 restricted gliadin epitope, identified for its activity on T cell clones, 8 9 was also active in the organ culture system of the treated coeliac mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…wheat, barley, and rye) give origin upon proteolytic digestion to biologically active antinutritional peptides able to adversely affect in vivo the intestinal mucosa of coeliac patients, whereas prolamins from other cereals (e.g. maize and rice) do not [30]. A large deal of cereal proteins originates from by-products following production of starch, malting or brewing industry.…”
Section: Biological Activities Of Plant Proteinsmentioning
confidence: 99%